Alternative lubricants: study on palm oil-based lubricants in metal forming process - Nurul, M. A. (Lembaga Minyak Sawit Malaysia, 2016)
Mineral oil-based lubricants are always the preferred choice for industrial application due to their excellent properties and reasonable price. However, due to environmental and depletion issues, a number of studies have been carried out to explore alternative lubricants such as plant oils. In metal forming processes, reducing frictions, improving tool life and product quality are some of the important issues to be considered. In our study, palm oil-based lubricants were tested for cold extrusion processes and mineral oils were used for comparison purposes. It was found that refined bleached deodorised (RBD) palm kernel oil and palm olein performed an enhanced extrusion load than mineral oil-based lubricant, and they showed no severe wear on product surface. Based on the results, renewable oil-based lubricants can be considered as a substitute to common mineral oil based lubricants used in the industry.